On-field identification and management of concussion in amateur rugby union - Brown, J (South African Journal of Sports Medicine, 2016)
Background: Rugby is a popular team sport and due to its contact nature carries a relatively high potential for injury, including concussion. Moreover, it is estimated that as much as 50% of concussions are not reported due to a variety of reasons, including not considering the injury to be sufficiently serious or not wanting to miss game time. Objectives: The aim of this brief review was to investigate and summarise current best practice for on-field identification and on-field management of concussion in amateur rugby. Methods: PubMed and ClinicalKey were searched between September and December 2014 for articles in the five years preceding the search dates. The latest versions of the Consensus Statement for Concussion in Sports and World Rugby’s concussion guidelines were also consulted. Results: Based on this search strategy, eight systematic reviews, one physician information article and four patient guidelines were investigated. Four reviews specifically described an “action plan” for on-field evaluation and management. Education of key stakeholders could reduce the number of unreported concussions. Once identified or suspected, concussions should be managed according to best practice procedures, which include removing the player from play immediately and consulting a medical doctor. If a medical doctor is not immediately available on the field tools such as the BokSmart on-field pocket “Concussion Guide”, and World Rugby’s “Pocket Concussion Recognition Tool”, are freely available online. Conclusion: Stakeholder education (including players, parents, teachers, coaches, referees, spouses) on both the on-field identification and management of concussions could reduce under-reporting and improve the overall management of concussed rugby players. Keywords: injury prevention, injury management, head injury, football